Aphis (Hemiptera, Aphididae) species living on Baccharis (Asteraceae) in southern South America, with description of three new species - Nafría, Juan Manuel Nieto; Ortego, Jaime; Brown, Paul A.; Ciruelos, Sara I. López; Durante, M. Pilar Mier (Zootaxa, 2019)
Aphid specimens belonging to the genus Aphis (Hemiptera, Aphididae, Aphidinae) collected on species of Baccharis (Asteraceae) in localities of Argentina and Chile, preserved in the Natural History Museum in London and in the Universidad de León collections, have been studied. They belong to six species: Aphis craccivora, Aphis gossypii and Aphis spiraecola, which are widely-distributed and polyphagous, and the new species: Aphis ingeborgae Nieto Nafría and Brown sp. n., Aphis conspicua Nieto Nafría and Mier Durante sp. n. and Aphis fuentesi Nieto Nafría and Ortego sp. n. which are here described from apterous and alate viviparous females, and also from oviparous females and males in the case of Aphis fuentesi. These six species plus the native and monophagous A. coridifoliae are those known in southern South America living on plants of Baccharis. Diagnostic features of new species and an identification key for apterous viviparous females of these seven species are presented.